Rare deleterious variants in genes involved in tissue structure and epithelial integrity are found in patients with group A streptococcal necrotising fasciitis by whole-exome sequencing - Parks, T; Elliott, K; Lamagni, T; Malinauskas, T; Murphy, M; Petherbridge, L; Guy, R; Auckland, K; Mentzer, A; Marsden, D; Strakova, L; Chapman, S; et al. (European Society of Clinical Microbiology and Infectious Disease, 2018)
Necrotising fasciitis (NF) is a rare manifestation of invasive Streptococcus pyogenes (GAS) infection associated with a substantial risk of death or disability. Hypothesising that host genetic factors might contribute, we sought to identify rare deleterious variants contributing to NF susceptibility.